Land, assets, and livelihoods: Gendered analysis of evidence from Odisha State in India - Savath, Vivien; Fletschner, Diana; Peterman, Amber; Santos, Florence (International Food Policy Research Institute, 2014)
Using data collected from the evaluation of two government land titling interventions in the Indian state of Odisha, this paper examines key relationships linking land and livelihood strategies. The investigation is one of the first to explicitly use the Gender, Agriculture, and Assets Project framework to gain additional insights on how gender–asset dynamics relate to household livelihood strategies.